Meaning and resilience in war-affected populations during crisis - Russo-Netzer, Pninit; Tarrasch, Ricardo; Saar-Ashkenazy, Rotem; Guez, Jonathan (Frontiers in Psychiatry, 2025)
IntroductionThe unprecedented events of October 7th, 2023, in Israel have profoundly impacted mental health and psychological functioning. This study aimed to explore how protective psychological factors—specifically meaning in life (MIL) and optimism—contribute to resilience in the context of wartime trauma. The study focused on identifying which protective factors most strongly predict resilience and psychological outcomes during collective trauma.MethodsA mixed-methods design was employed, combining quantitative and qualitative approaches. The quantitative sample included 758 participants from a national cohort. Stepwise multiple regression analyses were conducted to identify significant predictors of resilience from protective factors including social support, prioritizing meaning, presence of meaning, optimism, and psychological distress indicators. In parallel, qualitative data were collected through participants’ written reflections, which were analyzed using thematic analysis to identify sources and perceptions of meaning during the war.ResultsRegression analyses revealed that six factors significantly predicted resilience, explaining 36% of the variance: optimism emerged as the strongest predictor (β = 0.31), followed by psychological distress (β = -0.17), prioritizing meaning (β = 0.13), concern about the state’s future (β = -0.09), presence of meaning (β = 0.10), and social support (β = 0.08). Thematic analysis revealed that participants derived meaning from activities such as volunteering, maintaining daily routines, nurturing relationships, and engaging in spiritual practices, all of which were associated with higher resilience scores.DiscussionThe integration of quantitative and qualitative findings underscores the central role of optimism and meaning-making in psychological resilience during collective trauma. Optimism emerged as the most influential protective factor, while meaning-related orientations and social support provided complementary contributions. The coherence between data sources strengthens construct validity and offers valuable theoretical and practical implications for interventions aiming to foster resilience in contexts of war and crisis.